2018
DOI: 10.1016/j.nicl.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Global network modulation during thalamic stimulation for Tourette syndrome

Abstract: Background and objectivesDeep brain stimulation (DBS) of the thalamus is a promising therapeutic alternative for treating medically refractory Tourette syndrome (TS). However, few human studies have examined its mechanism of action. Therefore, the networks that mediate the therapeutic effects of thalamic DBS remain poorly understood.MethodsFive participants diagnosed with severe medically refractory TS underwent bilateral thalamic DBS stereotactic surgery. Intraoperative fMRI characterized the blood oxygen lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…To summarize our findings, the tic suppression networks appear to be mainly limbic and associative. This is in line a recent study investigating the effect of thalamic deep brain stimulation in GTS ( Jo et al, 2018 ). Ultimately, GTS might be best considered as a social decision-making network disorder, instead of a BG disorder, as was recently proposed because patients can choose to alter or inhibit tics in social contexts( Albin, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To summarize our findings, the tic suppression networks appear to be mainly limbic and associative. This is in line a recent study investigating the effect of thalamic deep brain stimulation in GTS ( Jo et al, 2018 ). Ultimately, GTS might be best considered as a social decision-making network disorder, instead of a BG disorder, as was recently proposed because patients can choose to alter or inhibit tics in social contexts( Albin, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study of intraoperative functional MRI demonstrated that thalamic stimulation in GTS patients has widespread effects on the frontostriatal, limbic, and motor networks. Motor tic reduction was correlated with suppression of motor and insula networks due to thalamic stimulation, while suppression of frontal and parietal networks correlated with vocal tic reduction ( Jo et al, 2018 ). In contrast, our study primarily found a limbic suppression strategy in GTS patients suppressing ocular tics.…”
Section: Discussionmentioning
confidence: 99%
“…We applied constant current (700 mA) biphasic chargedbalanced rectangular pulses, pulse width 100 or 200 ms (100 ms in animal 1, 2 and 4 while 200 ms in animals 3, 5e7), to the VL thalamus using an isolated pulse stimulator (Model 2100, A-M Systems, Carlsborg, WA). Based on our previous study [59] identifying the time course and saturation of stimulation at 50 Hz, here stimulation was applied for 3 s at 7 different frequencies (10,20,30,40,60,80 and 100 Hz). In all experiments, charge density was kept below the level which causes tissue damage [61].…”
Section: Stimulation and Recording Protocolmentioning
confidence: 99%
“…TS is also associated with neuropsychiatric comorbidities and has critical dysfunction of frontal, limbic, and motor networks . Jo and colleagues investigated the functional global connectivity of 5 TS patients in response to bilateral thalamic DBS of the centromedian and parafasicularis complex (CMPf) . The CMPf is a unique target in that its location allows connectivity into the sensory, motor, and limbic circuitries .…”
Section: Tourette's Syndromementioning
confidence: 99%